Risks of Mortality in New-Onset Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
Investigators at Lurie Children's Hospital of Chicago; Mayo Clinic, Rochester, MN; and centers in Connecticut, the Netherlands and Nova Scotia, pooled data from 4 large pediatric cohorts and obtained direct estimates of the mortality risk overall and from specific causes of mortality, particularly seizure related SUDEP.